Sustainable Development Goal Drivers in Food Systems - Kretschmer, Sebastian; Kahl, Johannes (Frontiers in Sustainable Food Systems, 2021)
Interacting driving forces in food systems, resulting in cumulative driver effects and synergies, induce non-linear processes in multiple directions. This paper critically reviews the discourse on driving forces in food systems and argues that mindset is the primary predictor for food system outcomes. In the epoch of sustainable development goals (SDGs) and the Anthropocene, mindset matters more than ever. Transformative narratives are beginning to transcend the dominant social paradigm, which is still driving the food system's overall trajectory. The psychosocial portrayal of the systemic mindset found in organic food systems presented in this paper “flips the script” and hypothesizes that worldview and paradigm have the most causal linkages with unsustainable driver synergies and reversely the biggest leverage on the mitigation thereof. Borrowing from ecological economics discourses, the paper sharpens the driver definition by applying the DPSIR analytical tool as a modified diagnostic framework and modeling approach for food systems. This research sheds new light on the nature of drivers of change, which are often portrayed as almighty and inevitable trends shaping food systems. Instead, it is proposed that drivers emerge from the actors' mindset, affecting food system behavior in a non-linear way. Mindset drives reinforcing feedback loops, resulting in vicious and virtuous cycles. These driver motives manifest in subsystems and continue to drive their interaction across food system elements. Mindset acts as an encapsulated input of food systems, all the while responding to feedback and releasing new drivers. A transformation framework along leverage points of the food system is presented that features the concept of SDG drivers.